Optimization Study of Adsorption Parameter for Removal of Dye Pollutant Using Candle Soot Coated Egg Carton. Issue 1 (December 2021) - Tai, Yong Kee; Sim, Lan Ching; Leong, Kah Hon; Saravanan, Pichiah
Abstract: In this study, several parameters that affect the adsorption capacity of Rhodamine B (RhB) dyes were reviewed which include initial pH, temperature, contact time and initial dye concentration. Experimental data was extracted from other literatures as input for subsequent optimization study. Design Expert version 11.1.2.0 software was used to find the optimal condition for adsorption of RhB dyes from wastewater by using candle soot coated on egg carton (CS-Egg) as absorbent. The Central Composite Design (CCD) in response surface methodology (RSM) was employed to perform the optimization and analysis process as it was effective in determining the optimal condition for the adsorption process. CCD evaluated many parameters at the same time and thus reducing the number of experiments required. The optimum condition to maximize the adsorption efficiency was obtained at pH 7, 262.5 mg/L, 60 min of contact time and 55 °C. The highest predicted adsorption efficiency of RhB dye was 90 % at optimum condition. The optimization of parameter provides a better understanding on the adsorption efficiency before conducting the actual experimental work.